Mastering Students’ Public Speaking Skill Through Psycholinguistic Aspect Using Qualitative Method - Yasin, Mohammad Ilham; Iman Jauhari; Gigih Dwi Ananto; Nur Laila Fitria (Universitas Kristen Cipta Wacana, 2025)
One of the most important communication skills that university students need to learn in order to be successful in their studies and careers is public speaking. Nonetheless, many students continue to experience psychological and linguistic obstacles, such as anxiety, a limited vocabulary, and trouble expressing their ideas orally. There is a paucity of research that takes a holistic approach to understanding how psycholinguistic mechanisms affect students' performance in public speaking, since current studies tend to concentrate on linguistic and pedagogical approaches separately. This study seeks to close this gap by examining how psycholinguistic variables—namely, cognitive processing, speech production processes, and emotional components—contribute to the development of students' public speaking abilities. The qualitative descriptive approach used in this study includes intentionally selecting students studying English Literature who have taken classes related to public speaking. Semi-structured interviews, classroom observations, and paperwork were used to gather the data. Miles and Huberman's interactive method, which involves data reduction, data presentation, and conclusion drawing, was used to evaluate the acquired data. According to the results, students' oral performance improves as they learn to manage their anxiety and become more conscious of psycholinguistics, which helps them with lexical retrieval, speech planning, and fluency. Using psycholinguistic-based approaches in instruction improves students' verbal expression and self-assurance. In order to advance public speaking proficiency, future research is advised to create training models based on psycholinguistics.